How vulnerable are road networks to shocks? An analysis through accessibility indicators - Angela Stefania Bergantino; Gianmarco Troiani; Tahseen Bashir; Francesca Pagliara (Sustainable Futures, 2025)
The purpose of the paper is to present an analysis of vulnerability of road networks through an accessibility indicator and a link importance index (LII). Specifically, the objective is to identify which traffic disruptions generate the most significant impacts. This methodology has been applied to three case studies, the medium-sized urban areas in southern Italy. The proposed accessibility indicator represents a measure of the vulnerability of an area, while the LII defines a hierarchy of importance among the roads of the network. The first indicator considers travel time and the distribution of jobs across the territory, while the second indicator depends on traffic flows. The output of the methodology consists of vulnerability maps, which show the most affected urban areas, and a ranking of the most important roads, obtained through the link importance index. This methodology is useful for transportation agencies, administrators, and civil protection, who should manage daily emergency situations following internal or external shocks such as traffic accidents or natural extreme events. Decision-makers can indetify the network's critical areas and develop programs to prioritize infrastructure improvements.